Results of experiments in animal production (1966/67 to 1975) (1976)
Presents findings of various animal production related experiments conducted under the auspices of the Ethiopian Institute of Agricultural Research at the Holetta, Bako, Adami Tulu, Melka Werer and Awassa research stations on the various indigenous breeds. Data on milk yields, calf rearing and post weaning, forage production and grazing trials, cattle fattening, feeding of crop residues, nutritive value of feeds as well as results of surveys on mastitis incidence, livestock diseases due to poor management and housing conditions included.